The Effectiveness of the Police's Role in Enforcing the Law Against Justice-Based Online Gambling Networks (A Case Study of the West Java Regional Police Cyber Directorate) - Muhammad Khoirul Iman; Andri Winjaya Laksana (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The rampant phenomenon of online gambling poses a serious challenge to law enforcement in Indonesia. Advances in digital technology are exploited by perpetrators to operate across borders with ever-evolving methods, demanding adaptation from law enforcement agencies. This study aims to: (1) Describe the role of the police in law enforcement against online gambling networks; (2) Analyze the weaknesses of this police role; and (3) Determine the level of effectiveness of justice-based law enforcement, with a case study on the Cyber Directorate of the West Java Regional Police. This research uses a socio-legal research method with a qualitative approach. Primary data was collected through interviews and observation at the Cyber Directorate of the West Java Regional Police, while secondary data was sourced from primary, secondary, and tertiary legal materials. Data analysis was conducted descriptively-qualitatively to understand the gap between law in books and law in action. The results indicate that the Police's role includes preventive efforts (site blocking, outreach) and repressive efforts (investigation, arrests). However, its effectiveness still faces significant weaknesses, such as a less adaptive legal framework, limitations in human resources and digital forensic technology, and the complexity of evidence gathering. It is concluded that effective and just law enforcement requires a holistic strategy that not only relies on a repressive approach but also strengthens preventive-educative aspects, inter-agency coordination, enhanced investigative capacity, and active community participation.